Does ALK‐rearrangement predict favorable response to the therapy of bevacizumab plus pemetrexed in advanced non‐small‐cell lung cancer? Case report and literature review. Issue 1 (9th January 2018) - Liu, Zhichao; Bao, Youting; Li, Butuo; Sun, Xindong; Wang, Linlin
Abstract: Background: Advanced ALK‐rearranged non‐small cell lung cancer (NSCLC) patients will develop acquired resistance after anaplastic lymphoma kinase (ALK) inhibitors therapies. Vascular endothelial growth factor‐A (VEGF‐A) production and tumor vessel formation were found to be more significantly enriched in ALK‐rearrangement NSCLC than that in epidermal growth factor receptor or Kirsten rat sarcoma viral oncogene mutated NSCLC. However, the correlation between ALK rearrangement and the efficacy of bevacizumab (a recombinant humanized IgG1 monoclonal antibody targeting VEGF‐A) was still elusive. Case presentation: We report a case with metastatic NSCLC harboring ALK‐rearrangement who was initially resistant to two courses of ALK‐Tyrosine Kinase Inhibitor (TKI) therapy, but got a clinical benefit of 7 months of progression free survival after the combined treatment of bevacizumab plus pemetrexed. And the patient tolerated well. Conclusions: It suggested that bevacizumab combined with pemetrexed might be a preferred option for ALK rearrangement patient who had failed no less than two courses of ALK‐TKIs.